Investigation of the relationship between human snx-2 protein and influenza virus rna polymerase enzyme in mammalian cells - TURAN, KADİR (My University, 2019)
Influenza A viruses are the viral pathogens that cause common upper respiratory diseases inhuman. These viruses change their genetic characteristics at high frequencies, which leads tothe emergence of new virus types, prevent vaccine protection and resistant to existing drugs.Therefore, alternative strategies should be developed to cope with influenza A viruses. In thiscontext, the elucidation of the relationship between influenza A virus and the host cell at themolecular level will be a guide in dealing with the viruses. It has been shown interactionbetween human sorting nexin-2 (SNX-2) protein and influenza virus RNA polymerase subunitPA by using yeast two hybrid method in our different project (TUBITAK, grant number:112S518). In this work it was aimed to reveal the relationship between influenza PA and theSNX-2 protein in human cells, and to demonstrate the importance of SNX-2 protein in terms ofinfluenza virus replication. For this purpose, HeLa and HEK293 cells originated from humanwere utilized. The physical interaction between viral PA protein and human SNX-2, whichtemporarily synthesized in the cells by plasmid transfection, was investigated byimmunoprecipitation and immunofluorescence methods. The endogenous SNX-2 protein levelin the cells was increased with transient transfection or reduced (knock-down) by gene-specificsiRNAs. The replication of influenza A virus were examined in these cells.Co-immunoprecipitation analyses revealed the interactions between virus PA and SNX-2protein in HEK293 cells. It was observed that the carboxyl-domains of SNX-2 has interact withviral PA protein. This result was also supported with immunofluorescence assay. Influenza viralreplication was positively affected in SNX-2 knock down cells. In contrast, the over-expressionof SNX-2 in the cells has not shown a significant effect on influenza virus replication. Theseresults suggest that SNX-2 have a negative regulatory effect on influenza virus replication.SNX-2 has a function in the vesicular trafficking. From this perspective, the question of howSNX-2 protein influences the influenza virus replication still remains to be answered.Keywords: Influenza, viral RNA polymerase, PA protein, SNX-2 protein*This work was supported by a grant from the scientific research foundation of MarmaraUniversity (grant number: SAG-C-YLP-120619-0224) and a grant from The Scientific andTechnological Research Council of Turkey (grant number: 112S518).
Keywords: Sağlık Bilimleri; Temel Bilimler; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Clinical Medicine (MED); Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary